Analyzing Dynamic Changes of Laboratory Indexes in Patients with Acute Heart Failure Based on Retrospective Study. (6th April 2016) - Wang, Yurong; Fu, Lei; Jia, Qian; Yu, Hao; Zhang, Pengjun; Zhang, Chunyan; Huang, Xueliang; He, Kunlun; Tian, Yaping
Abstract : Background . Changes of N-terminal probrain natriuretic peptide (NT-proBNP) have been studied whether in the long term or the short term in patients of acute heart failure (AHF); however, changes of NT-proBNP in the first five days and their association with other factors have not been investigated. Aims . To describe the dynamic changes of relevant laboratory indexes in the first five days between different outcomes of AHF patients and their associations. Methods and Results . 284 AHF with dynamic values recorded were analyzed. Changes of NT-proBNP, troponin T, and C-reactive protein were different between patients with different outcomes, with higher values in adverse group than in control group at the same time points (p < 0.05 ). Then, prognostic use and risk stratification of NT-proBNP were assessed by receiver-operating characteristic curve and logistic regression. NT-proBNP levels at day 3 showed the best prognostic power (area under the curve = 0.730, 95% confidence interval (CI): 0.657 to 0.794) and was an independent risk factor for adverse outcome (odds ratio, OR: 2.185, 95% CI: 1.584–3.015). Classified changes of NT-proBNP may be predictive for adverse outcomes in AHF patients. Conclusions . Sequential monitoring of laboratory indexes within the first 5 days may be helpful for management of AHF patients.